Pengembangan Media Scrapbook Cerita Fiksi Berbasis Kearifan Lokal Suku Sasak Di TK Negeri Pembina Ampenan - Auliyah, Rita Lutfiah; Musdat, Syaiful; Tahir, Muhammad; Rachmayani, Ika (Mataram University, 2025)
This study aims to develop a fictional storybook that incorporates the local wisdom of the Sasak ethnic group, specifically focusing on the legend of Putri Mandalika. The primary goal is to use this storybook as a learning aid to enhance early childhood language development at Taman Kanak-kanak Negeri Ampenan Pembina. A Research and Development (R&D) methodology was employed using the 4D development model: define, design, develop, and disseminate. In the Define stage, teachers conducted needs analyses through interviews and observations to identify learning materials appropriate to the students’ characteristics and language development. To provide relevant and engaging learning experiences, the researcher produced story content, graphics, and visual components related to Sasak cultural elements during the Design stage. In the Develop stage, media and material experts conducted validation. The validation results showed scores of 84% from the material expert and 77% from the media expert, both categorized as “very effective.” The average score from a small-group trial involving 15 students was 90%. Based on these findings, the developed scrapbook media can serve as an alternative educational tool that integrates local cultural values and proves highly effective in improving early childhood language skills.